Effectiveness of the cardiac-diabetes transcare program: protocol for a randomised controlled trial. Issue 1 (December 2017) - Wu, Chiung-Jung; Atherton, John; MacIsaac, Richard; Courtney, Mary; Chang, Anne; Thompson, David; Kostner, Karam; MacIsaac, Andrew; d'Emden, Michael; Graves, Nick; McPhail, Steven
Abstract Background This paper presents a protocol for a randomised controlled trial of the Cardiac-Diabetes Transcare program which is a transitional care, multi-modal self-management program for patients with acute coronary syndrome comorbid with type 2 diabetes. Prior research has indicated people hospitalised with dual cardiac and diabetes diagnoses are at an elevated risk of hospital readmissions, morbidity and mortality. The primary aim of this study is to evaluate the effectiveness (and cost-effectiveness) of a Cardiac-Diabetes Transcare intervention program on 6-month readmission rate in comparison to usual care. Methods/Design A two-armed, randomised controlled trial with blinded outcome assessment will be conducted to evaluate the comparative effectiveness of two modes of care, including a Usual Care Group and a Cardiac-Diabetes Transcare Intervention (in addition to usual care) Group. The primary outcome is 6-month readmission rate, although a range of secondary outcomes will be collected (including self-efficacy) at baseline, 1, 3 and 6 month reassessments. The intervention group will receive in-hospital education tailored for people recovering from an acute coronary syndrome-related hospital admission who have comorbid diabetes, and they will also receive home visits and telephone follow-up by a trained Research Nurse to reinforce and facilitate disease-management-related behaviour change. Both groups will receive usual care interventions offered or referred from participating hospital facilities. A sample size of 432 participants from participating hospitals in the Australian states of Queensland and Victoria will be recruited for 90% power based on the most conservative scenarios modelled for sample size estimates. Discussion The study outlined in this protocol will provide valuable insight into the effectiveness of a transitional care intervention targeted for people admitted to hospital with cardiac-related presentations commencing in the inpatient hospital setting and transition to the home environment. The purpose of theory-based intervention comprising face-to-face sessions and telephone follow up for patients with acute coronary syndrome and type 2 diabetes is to increase self-efficacy to enhance self-management behaviours and thus improve health outcomes and reduce hospital readmissions. Trial registration This study has been registered with the Australian New Zealand Clinical Trials Registry dated 16/12/2014:ACTRN12614001317684 .